Biological maturation and its impact on overhand shot technique among young badminton players - Ramli, Alif Syamim Syazwan; Tengku Kamalden, Tengku Fadilah; Sharir, Raihana; Harith, Hazreen Haizi; Hanafi, Marsyita (Human Resource Management Academic Research Society, 2020)
Overhand shot technique is the most prevalent technique in badminton and is often emphasized by coaches during training. However an overemphasis on a particular technique might have a different impact on young badminton players who is undergoing puberty period. Previous studies had mentioned little on the impact of biological maturation in influencing sports technique. The aim of this paper is to review the overhand shot technique in badminton among young badminton players in the context of biological maturation impact. This includes the relationship between biological maturation, physical growth and overhand shot technique. The existing literatures have highlighted the potential impact of biological maturation on sport technique, particularly badminton overhand shot among young players. More in depth studies are needed on the impact of biological maturation in young badminton players on technical execution of the overhand shot for better understanding on this matter. Such work can be useful in ensuring an excellent shot technical proficiency and hence increase chance of winning the match in badminton among young badminton players.